Effect of modifying concentrations of calcium and magnesium on in vitro development of banana CV. Prata-Anã (Genomic group AAB) (Bioscience Journal, 2017)
Research suggests that the development of micropropagated banana plants can be improved by altering nutrient concentrations in the culture medium. The aim of this study was to evaluate the in vitro development of banana plants exposed to varying concentrations of calcium and magnesium sulfate. The shoot tips of banana cv. Prata-Anã were inoculated in flasks (volume, 250 cm3) containing 50 mL of MS culture medium. The culture medium contained varying concentrations of CaCl2 (0, 220, 440, 880 mg L-1) and MgSO4 (0, 185, 370, 740 mg L-1. A completely randomized experimental design was employed, based on a 4 Ã— 4 factorial scheme (four levels of CaCl2 concentration, and four of MgSO4). The MS culture medium containing 880 mg L-1 of CaCl2 but no MgSO4 showed the highest increment in the number of leaves (6.0). The highest number of roots was observed in the absence of CaCl2 and MgSO4 in the medium. Additionally, the shoot length was longer (5.05 cm) when the MS medium was supplemented with 185 mg L-1 of MgSO4. The optimum in vitro development of banana cv. Prata-Anã was obtained when the MS medium was supplemented with 880 mg L-1 of CaCl2 and 370 mg L-1 of MgSO4.